2015
DOI: 10.1088/0957-4484/26/29/295202
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-selective absorptance in GaAs, InP and InAs nanowire arrays

Abstract: The absorptance in vertical nanowire (nw) arrays is a result of three optical phenomena: radial mode resonances, near-field evanescent wave coupling, and Fabry-Perot (F-P) modes. The contribution of these optical phenomena to GaAs, InP and InAs nw absorptance was simulated using the finite element method. The study compared the absorptance between finite and semi-infinite nw lengths with varying geometrical parameters, including the nw diameter, length and array period. Simulation results showed that the reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 23 publications
5
48
0
Order By: Relevance
“…We assume a terrestrial solar cell at a temperature T = 300 K throughout. Many previous studies have considered a square array of nanowires [19][20][21]. Here, we choose to consider a hexagonal array (Figure 1) since there, the nanowire surface coverage is 15 % higher for given pitch P, which is beneficial for absorption of light if P is fixed between the square and hexagonal array (Supplementary Information Figure S1).…”
Section: Nanowire Array Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…We assume a terrestrial solar cell at a temperature T = 300 K throughout. Many previous studies have considered a square array of nanowires [19][20][21]. Here, we choose to consider a hexagonal array (Figure 1) since there, the nanowire surface coverage is 15 % higher for given pitch P, which is beneficial for absorption of light if P is fixed between the square and hexagonal array (Supplementary Information Figure S1).…”
Section: Nanowire Array Geometrymentioning
confidence: 99%
“…III-V nanowire arrays show strong diffraction of light, in which case the regular Beer-Lambert law of bulk absorption does not apply [19][20][21][22][23]. Through measurements, it was shown that a nanowire array can absorb almost all the incident light, even if the nanowires cover only 10 % of the surface [24].…”
Section: Optical Considerationsmentioning
confidence: 99%
“…There is a need for fast, accurate modeling tools to enable rapid exploration and optimization of nanowire designs. Conventionally, finite element [4,[9][10][11] and finite difference methods [1,12,13] have been used in optical models of NWSC. While these techniques are highly accurate, they are computationally expensive, limiting their usefulness in a closed-loop global device optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, enhanced absorptance was studied for optical modes parallel to the NWs axis, exceeding that of planar structures. 195 The refractive index contrast also plays a crucial role in the modal resonance absorption, causing the optical absorption to be higher than thin film structures. 196 Moreover, NW photodetectors showed superior sensitivity compared with the planar devices, due to the high surface-to-volume ratio that leads to larger photoconductive gain.…”
Section: Solar-blind Algan-based Nanowires-photodetectorsmentioning
confidence: 99%